Factors associated with COVID-19 vaccine uptake in a US/Mexico border community: demographics, previous influenza vaccination, and trusted sources of health information - Lomeli, Angel; Escoto, Arleth A.; Reyes, Breanna; Burola, Maria Linda M.; Tinoco-Calvillo, Stephenie; Villegas, Isabel; Cohen, Ariel S.; Laurent, Louise C.; Salgin, Linda; Stadnick, Nicole A.; Rabin, Borsika; Seifert, Marva (Frontiers in Public Health, 2023)
Background COVID-19 vaccine uptake has been uneven, particularly across racial/ethnic and age groups. This study seeks to understand factors associated with COVID-19 vaccine uptake in a large cross-sectional sample of predominantly Latinos/Latinas individuals living near the US/Mexico border. Methods Data are extracted from a 176-item survey conducted as part of a parent study focused on the co-creation of a COVID-19 testing program for underserved communities developed through a partnership between an academic institution and a Federally Qualified Health Center. The following participant variables were examined: health history, COVID-19 symptoms, COVID-19 testing and vaccine experiences, and perceptions of sources of health information. Participant characteristics were compared using chi-square tests. Multivariate logistic regressions were used for the final statistical model. Results From 1 May 2021 to 30 April 2022, 4,964 adults, 66% of whom were identified as women, completed the survey. Approximately 80% of participants reported having received at least one COVID-19 vaccine. Female sex, older age, Hispanic/Latino(a) ethnicity, previous influenza vaccination, advanced education, and perceived elevated risk of COVID-19 were significantly (p < 0.05) associated with having received a COVID-19 vaccine. Regarding sources of health information, individuals who indicated they trust their doctor, healthcare provider, or the US government “a great deal” were more likely to have received a COVID-19 vaccine compared to individuals who indicated that they trusted these sources “not at all.” In contrast, those who reported having “a great deal” of trust in their faith leader or their social media contacts were significantly less likely to have received a COVID-19 vaccine than those who reported that they trusted these sources “not at all.” Conclusion Sex, education, past influenza vaccination, perceived risk of COVID-19 infection, and trust in specific sources of information were correlated with the uptake of COVID-19 vaccination. Additional research is needed to better understand why this confluence of factors, particularly the unique findings about trusted sources of information, are associated with vaccine uptake. Understanding these associations, specifically within underserved, Latino/Hispanic communities, is an important first step to inform efforts aimed at increasing and sustaining COVID-19 vaccine uptake and adoption of other public health interventions.